Lexicons of Song Used in Palawakya Dance - Putu Diandra Dama Suri; I Gede Budasi; Putu Eka Dambayana (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Palawakya dance is one of the traditional dances in Bali. The accompaniment of the dance is a set of gong kebyar, one of the typical of Balinese gong music. The present study aimed to analyses lexical meaning of the song lyrics of the dance, the kind of language used in the song, the typical of lexicons and their word clasess. This descriptive qualitative study applied observing, interviewing, and documentation techniques to find its study data. This study using three instruments including the researcher, observation sheet, and interview guide were used to collect the obtained data of this study. The subjects of the study were the ones who are experts in singing of song performed in the Palawakya dance. The object of the study is the lexicons which exist in the song of the dance. The study results show that the song  used in the dance tells the story of Rama's journey at the boarding school in Ayodhya Kingdom to learn  self defense in an attempt to destroy his annoying enemies. There were 11 lexicons in the song and all of them are classified into noun class of word. This study implicates to the contribution to language preservation. Moreover, it can be a reminder that some certain lexicons are endangered so the involvement of both government and society is needed.